Pathway Analysis using Gene-expression Profiles of HPV-positive and HPV-negative Oropharyngeal Cancer Patients in a Hispanic Population: Methodological Procedures - Suárez, Erick; González, Lorena; Pérez-Mitchell, Carlos; Ortiz, Ana P.; Ramírez-Sola, Maricarmen; Acosta, Jaime; Bernabe-Dones, Raúl D.; González-Aquino, Carlos; Montes-Rodríguez, Ingrid; Cadilla, Carmen L. (Puerto Rico Health Sciences Journal, 2016)
Objective: The incidence of oral cavity and pharyngeal cancer in Puerto Rican men is higher than it is in the men of any other ethnic/racial group in the United States of America (US). The information regarding the effect of the human papilloma virus (HPV) in the gene-expression profile among patients with this cancer is limited in Hispanic community. We aim to describe the methodology for future studies to identify the molecular networks for determining overrepresented signaling and metabolic canonical pathways, based on the differential gene-expression profiles of HPV+ and HPV- samples from patients with oropharyngeal squamous cell carcinoma in Puerto Rico. Methods: We analyzed the RNA expression of 5 tissue samples from subjects diagnosed with oropharyngeal squamous cell carcinoma, 2 HPV+ and 3 HPV-, using Affymetrix GeneChips. The relative difference between the average gene expressions of the HPV+ and HPV- samples was assessed, based on the fold change (log2-scale). Results: Our analysis revealed 10 up regulated molecules (Mup1, LRP1, P14KA, ALYREF, and BHMT) and 5 down regulated ones (PSME4, KEAP1, ELK3, FAM186B, and PRELID1), at a cutoff of 1.5-fold change. Ingenuity Pathway Analysis showed the following biological functions to be affected in the HPV+ samples: cancer, hematological disease, and RNA post-transcriptional modification. QRT-PCR analysis confirmed only the differential regulation of ALYREF, KEAP1, and FAM186B genes. Conclusion: The relevant methodological procedures described are sufficient to detect the most significant biological functions and pathways according to the HPV status in patients with oropharyngeal cancer in Puerto Rico.